Test Anxiety Beliefs as Predictor of Students’ Achievement in Chemistry in Public Secondary Schools in Kenya - Oluoch, James Ndege; Aloka, Peter J. O.; Odongo, Benson Charles (Scientific and Academic Publishing, 2018)
The present study was designed to determine the extent to which test anxiety beliefs predicted achievement in chemistry among students in public secondary schools in Kenya. The study was guided by Eccles-Wigfield’s Expectancy-Value theory of motivation. The study adopted concurrent embedded design. A sample of 353 form for students, 10 chemistry and 10 guidance and counseling teachers was selected from 26 public secondary schools from Rachuonyo South Sub County in Homa Bay County using both Stratified random sampling and purposive sampling techniques. Data collection was done using questionnaire and interview schedule. Questionnaire was adapted from Test Anxiety Inventory (TAI) By Spielberger (1980). Quantitative data was analyzed both descriptively and inferentially (Pearson Product Moment Correlation, multiple regression and ANOVA) while qualitative data was analyzed using thematic analysis. Pearson Product Moment revealed that there was statistically significant negative correlation (r= - .432, n=308, P< .05) between test anxiety and Chemistry academic and that test anxiety accounted for 18.7% (R2=.184) of the variation in performance in chemistry Academic. The study recommended that there is need for curriculum and efforts towards guidance and counseling in schools to include strategies of coping with test anxiety in the guidance and counseling programs alongside the education policies in Kenya relating to guidance and counseling. This is because test anxiety negatively affects chemistry academic achievement and learners who are at risk of developing test anxiety may end up performing poorly in chemistry exam.
Keywords: Test anxiety beliefs; Chemistry academic achievement; Secondary school students; Kenya